Pioggia e acqua - Icardi, Mauro (Chimica nella Scuola, 2024)
When we reflect on water, we too often only concern ourselves with the effects that scarcity or compromised quality may have on the human community. The comments I read on articles dealing with the drought issue are totally anthropocentric. The drought problem is commented on with the idea that it is technological innovations that will solve the problem, as if personal attention and commitment take second place when it comes to having the necessary respect and care in the use of water. If we educate ourselves all together to use water carefully, without wasting a single drop, taking care of it, if we learn to know and respect it, if we know it better, we will help the only planet we have. In such a way, we will also be better people, people who, when they wake up and see that it is raining, no longer snort because there is bad weather outside, but think about how wonderful the water cycle is that quenches the thirst of our only planet.